2016
DOI: 10.1371/journal.pone.0164807
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Cardiovascular Autonomic Neuropathy Predicts Recurrent Cardiovascular Diseases in Patients with Type 2 Diabetes

Abstract: Cardiovascular autonomic neuropathy (CAN) is a risk factor for cardiovascular disease (CVD) and mortality in patients with type 2 diabetes. This study evaluated the relationship between CAN and recurrent CVD in type 2 diabetes. A total of 206 patients with type 2 diabetes who had a history of CVD within 3 years of enrollment were consecutively recruited from January 2001 to December 2009 and followed-up until December 2015. Cardiovascular autonomic function tests were performed using the following heart rate v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…Moreover, the clinical utility of VM and LS which we found pivotal in autonomic testing is confirmed by the paper of May and Arildsen [3] which shows the high independent predicting mortality value of VM and LS, while the deep breathing test results useless; just on the line and confirming what recently has come from the DIAD study, as mentioned in our paper [4,5]. Therefore, at least one question arises from our paper and other recent evidences: is it necessary to use the deep breathing test anymore?…”
Section: Dear Editorsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, the clinical utility of VM and LS which we found pivotal in autonomic testing is confirmed by the paper of May and Arildsen [3] which shows the high independent predicting mortality value of VM and LS, while the deep breathing test results useless; just on the line and confirming what recently has come from the DIAD study, as mentioned in our paper [4,5]. Therefore, at least one question arises from our paper and other recent evidences: is it necessary to use the deep breathing test anymore?…”
Section: Dear Editorsupporting
confidence: 87%
“…We appreciated that they reached somewhat similar conclusions in a previous work [2]: i.e., the association of HRV on Valsalva manoeuvre (VM) and on lying to standing (LS) is the most reliable tests for autonomic dysfunctions, although we found VM more sensitive than LS, in contrast to what they found.However, we need to underline an important feature of our work: it is based on the ability of each test to recognize the presence "in the real world" of autonomic neuropathy, i.e., documented by the relief of postural hypotension. This marks an important difference from other previously published papers cited by K. Pafili and N. Papanas which, however, were based on "self-controlled" calculations within the five Ewing's tests: i.e., comparing the sensitivity (and specificity) of each test with the other tests in cross correlations within the battery itself in a questionable "closed loop".Moreover, the clinical utility of VM and LS which we found pivotal in autonomic testing is confirmed by the paper of May and Arildsen [3] which shows the high independent predicting mortality value of VM and LS, while the deep breathing test results useless; just on the line and confirming what recently has come from the DIAD study, as mentioned in our paper [4,5]. Therefore, at least one question arises from our paper and other recent evidences: is it necessary to use the deep breathing test anymore?Hence, following our approach, the diagnosis in cardiovascular autonomic neuropathy results, we would say, simpler and clearer too.…”
supporting
confidence: 87%
“…1 CAN results from damage to the autonomic nerve fibers that innervate heart and vessels and causes abnormalities in heart rate control and vascular dynamics with increasing risks of silent myocardial ischaemia 2,3 and recurrent cardiovascular disease (CVD). 4,5 In addition, CAN was the strongest predictor for mortality during a 7-year follow-up in people with type 1 diabetes compared with traditional cardiovascular risk factors. 6 Several recent studies indicated that glycaemic variability (GV) is associated with CAN independent of mean glucose in poorly controlled 7,8 and newly diagnosed 9 type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular autonomic neuropathy (CAN) is a common chronic complication of diabetes mellitus . CAN results from damage to the autonomic nerve fibers that innervate heart and vessels and causes abnormalities in heart rate control and vascular dynamics with increasing risks of silent myocardial ischaemia and recurrent cardiovascular disease (CVD) . In addition, CAN was the strongest predictor for mortality during a 7‐year follow‐up in people with type 1 diabetes compared with traditional cardiovascular risk factors .…”
Section: Introductionmentioning
confidence: 99%
“…2 Cardiovascular autonomic neuropathy is also an independent risk factor for silent ischemia, myocardial dysfunction, and major cardiovascular events. [3][4][5][6] In addition, definite CAN is not only a predictor for recurrent cardiovascular disease, 7 but has been also associated with increased all-cause mortality in diabetic patients. 8 There have been several studies of nocturnal arrhythmias associated with sudden death or dead-in-bed syndrome.…”
Section: Introductionmentioning
confidence: 99%